Cognitive Development in Children Aged 2-3 Years with Stunting in Kediri - Idola Perdana Sulistyoning Suharto; Susmiati; Endang Mei Yunalia; Devangga Darma Karingga; Angeline Bushy; Ines Septiya Prayogi (Universitas STRADA Indonesia, 2026)
Background: In the first 1,000 days of life, children are vulnerable to chronic malnutrition, known as stunting, which impacts cognitive development. An initial survey in Blabak Village, Kediri City, on several stunted children showed language delays, difficulty concentrating, motor delays and understanding commands, which means they tend to experience cognitive disorders. Purpose: The study aim is to analyze the relationship between stunting and cognitive development in children aged 2–3 years. Methods: This research using correlation analytical research design with cross-sectional approach. Sample of 54 children aged 2-3 years, selected using proportionate stratified random sampling. The research was conducted at 6 integrated health service post (posyandu), Blabak Village, Kediri City in September 2024. Stunting as an independent variable, while cognitive development as a dependent variable. Data were analyzed using Spearman rho test. Results: The results of Spearman's rho between stunting and cognitive development in learning and problem solving category, logical thinking, symbolic thinking sequentially have P values of 0.000; 0.000; and 0.005. The correlation coefficient between Stunting and Cognitive Development in Learning and Problem Solving Category, Logical Thinking, Symbolic Thinking sequentially is 0.651; 0.650; 0.374. Conclusion: There is a significant relationship between stunting and cognitive development in learning and problem solving category (strong relationship), logical thinking (strong relationship), symbolic thinking (quite strong relationship).